1997
DOI: 10.1002/pro.5560060801
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of specificity in the cysteine protease cruzain

Abstract: The structure of cruzain, an essential protease from the parasite Trypunosomu cruzi, was determined by X-ray crystallography bound to two different covalent inhibitors. The cruzain S2 specificity pocket is able to productively bind both arginine and phenylalanine residues. The structures of cruzain bound to benzoyl-Arg-Ala-fluoromethyl ketone and benzoyl-Tyr-Ala-fluoromethyl ketone at 2.2 and 2.1 A, respectively, show a pH-dependent specificity switch. Glu 205 adjusts to restructure the S2 specificity pocket, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
219
0
20

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(252 citation statements)
references
References 29 publications
13
219
0
20
Order By: Relevance
“…During the intracellular amastigote stage of the T. Cruzi life cycle, cruzain is present on the surface of the parasite where the pH of the host cytoplasm is almost neutral (pH 7.4). 32 Thus, hydrogen atoms were added at this physiological pH using fDYNAMO library, 57 according to the pKa values of the residues of 1AIM structure calculated within the empirical PROPKA 3.1 program of Jensen et al [58][59][60] Fluor and chlorine atoms were added using Pymol 61 to create the two systems under study: Bz-Tyr-Ala-CH 2 F and Bz-Tyr-Ala-CH 2 Cl. A total of 12 counter ions (Na + ) were placed into optimal electrostatic positions around both systems, in order to obtain electro neutrality.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…During the intracellular amastigote stage of the T. Cruzi life cycle, cruzain is present on the surface of the parasite where the pH of the host cytoplasm is almost neutral (pH 7.4). 32 Thus, hydrogen atoms were added at this physiological pH using fDYNAMO library, 57 according to the pKa values of the residues of 1AIM structure calculated within the empirical PROPKA 3.1 program of Jensen et al [58][59][60] Fluor and chlorine atoms were added using Pymol 61 to create the two systems under study: Bz-Tyr-Ala-CH 2 F and Bz-Tyr-Ala-CH 2 Cl. A total of 12 counter ions (Na + ) were placed into optimal electrostatic positions around both systems, in order to obtain electro neutrality.…”
Section: Computational Modelmentioning
confidence: 99%
“…Inhibition of cruzain activity with fluoromethyl ketone-based inhibitors seems to be correlated with the loss of feasibility of parasites in both ex-vivo tissue culture and in vivo mouse models. 19,32,33 Information derived from the study of the molecular mechanism of hydrolysis catalyzed by cysteine proteases could be used as starting point to explore the inhibition mechanism at atomistic level. Early studies revealed a participation of the residues Cys25 and His159 (cruzain numbering) from the active site of theses proteases.…”
Section: Introductionmentioning
confidence: 99%
“…As NA larvae too traces migratory route through blood capillaries of human hosts, the cathepsin B-like cysteine proteases of the human hookworm were scrutinized for molecular features which could be responsible for kallikrein-like activity. This was done by aligning the secretory NA CPs with the sequences in the Protein Data Bank (PDB) [43] deposited structures of human cathepsin B (ID: 1HUC) and cathepsin L-like cruzain, (ID: 2OZ2) -both of which share similar substrate specificity that has been attributed to a critical Glu placed at their S2 subsites, in the protease structures [44] . The sequences were aligned in ICM with the same parameters as mentioned before.…”
Section: Molecular Feature Detection For Kallikrein-like Activitymentioning
confidence: 99%
“…2b). Using iceLogo software (Gillmor et al 1997), the P4 to P4ʹ substrate signature was generated using all cleavage sites detected after 60 minutes incubation.…”
Section: Proteomic Analysis Of Gastric Juicementioning
confidence: 99%
“…These studies have determined that Leu-67, Ala-133 and Leu-157 form the S2 pocket of this enzyme (McGrath et al 1995). In addition, it is known that Glu-205 rotates out of the S2 pocket upon binding of large amino acids such as phenylalanine (Gillmor et al 1997). H. americanus cathepsin L3 possesses a tryptophan at position 67 (papain numbering) and identical residues at positions 133, 157 and 205 (Fig.…”
Section: Sequence and Specificity Comparison Of H Americanus Cathepsmentioning
confidence: 99%